Pengaruh Motivasi Kerja, Lingkungan Kerja, dan Disiplin Kerja terhadap Kinerja Karyawan : Studi pada Karyawan PT Wisata Titiannusantara Pelangi, Jakarta Barat - Gifa Inayah; Hari Subagio (Jurnal Manajemen Bisnis Era Digital, 2025)
Employee performance is a crucial factor in supporting a company's success, particularly in the tourism sector, which demands optimal human resource quality. Factors such as work motivation, work environment, and work discipline are believed to significantly influence employee performance. However, the extent to which these three factors contribute to improved employee performance in tourism companies still requires empirical research. This study aims to determine the partial effect of work motivation, work environment, and work discipline on employee performance at PT. Wisata Titiannusantara Pelangi. The study population comprised all 40 employees, with the sampling technique using the saturation method (sampling the entire population). Data analysis was performed using multiple linear regression processed using SPSS version 22. The results show that work motivation has a positive and significant effect on employee performance, meaning that the higher an employee's motivation, the better their performance. The work environment also proved to have a positive and significant effect on performance, indicating that a comfortable and supportive work environment can improve employee performance. Furthermore, work discipline has a positive and significant effect on employee performance, indicating that discipline in carrying out tasks contributes significantly to achieving optimal work results. Overall, this study confirms that motivation, work environment, and work discipline are important factors that must be considered by management in efforts to improve employee performance, especially in companies operating in the tourism sector.